ANALISIS PRODUKSI PROGRAM PODCAST “MILENIAL TALK” DALAM TAYANGAN YOUTUBE DISKOMINFO KOTA PADANG - Ashshidiqi, Muhammad Irsyad; Maijar, Andri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem in this thesis is the production process of the Podacst Millennial Talk program in the Padang City Diskominfo YouTube broadcast. The purpose of this discussion is to find out the production process for the Millennial Talk Podcast Program. The type of research that researchers use is qualitative research with descriptive analysis. To obtain data from the problems being studied, the data collection techniques that researchers use are through observation, interviews and documentation. Analyzing data is carried out descriptively, then it is described and classified into certain aspects of the problem and explained in effective sentences. Based on the research results, it was found that the Millennial Talk Podcast Program Production Process had been implemented from the Pre-Production Stage, Program Production, to Post-Production Program, and was Running Well. The Program Production Team has made efforts to present interesting shows for each production by maintaining the quality of the shows, creating highlights or broadcasting excerpts from shows via the Instagram platform, as well as creating promotional posters containing program information that will be broadcast via the Instagram platform.